Demographic, clinical and lifestyle-related correlates of accelerometer assessed physical activity and fitness in newly diagnosed patients with head and neck cancer. (3rd March 2020) - Douma, J. A. J.; Verdonck-de Leeuw, I. M.; Leemans, C. R.; Jansen, F.; Langendijk, J. A.; Baatenburg de Jong, R. J.; Terhaard, C. H. J.; Takes, R. P.; Chinapaw, M. J.; Altenburg, T. M.; Buffart, L. M.
Abstract: Introduction: Objective measurements of levels of physical activity and fitness in patients with head and neck cancer (HNC) are lacking. Furthermore, demographic, clinical and lifestyle-related correlates of low levels of physical activity and fitness in patients with HNC are unknown. This study aims to investigate the levels of accelerometer that assessed physical activity and fitness in patients with HNC and to identify their demographical, clinical and lifestyle-related correlates. Methods: Two hundred and fifty-four patients who were recently diagnosed with HNC and participated in the NETherlands QUality of life and Biomedical cohort studies In head and neck Cancer (NET-QUBIC) study were included. Physical activity (accelerometer), cardiorespiratory fitness (Chester Step Test), hand grip strength (hand dynamometer) and lower body muscle function (30-second chair-stand test) were assessed. Multivariable linear regression analyses with a stepwise forward selection procedure were used. Results: Patients spent 229 min/d in physical activity of which 18 min/d in moderate-to-vigorous physical activity. The mean predicted VO2 max was 27.9 ml/kg/min, the mean hand grip strength was 38.1 kg and the mean number of standings was 14.3. Patients with lower educational level, more comorbidity and higher tumor stage spent significantly less time in physical activity. Older patients, females and patients with a higher tumor stage had significantly lower cardiorespiratory fitness levels. Older patients, females, patients with more comorbidity, patients with normal weight and patients who have never smoked had significantly lower hand grip strength. Older patients, patients with lower educational level, smokers and patients with more comorbidity had a significantly lower function of lower body muscle. Conclusions: Pre-treatment levels of physical activity, cardiorespiratory fitness and lower body muscle function are low in patients with HNC. Based on this study, exercise programs targeted and tailored to patients with low levels of physical activity and fitness can be developed.